2007
DOI: 10.1016/j.abb.2006.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate and invertebrate carotenoid-binding proteins

Abstract: In invertebrates and vertebrates, carotenoids are ubiquitous colorants, antioxidants, and provitamin A compounds that must be absorbed from dietary sources and transported to target tissues where they are taken up and stabilized to perform their physiological functions. These processes occur in a specific and regulated manner mediated by high-affinity carotenoid-binding proteins. In this minireview, we examine the published literature on carotenoid-binding proteins in vertebrate and invertebrate systems, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 78 publications
1
60
0
Order By: Relevance
“…The incorporation of carotenoids into membranes is governed by their polarity and stereometry [39,53]. The localization and orientation of the xanthophylls within the lipid membrane are determined by the localization of the non-polar polyene chain, and by the localization of the hydrophilic groups, which remain in contact with the polar head groups of the lipid bilayer [40].…”
Section: Macula Lutea Pigmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of carotenoids into membranes is governed by their polarity and stereometry [39,53]. The localization and orientation of the xanthophylls within the lipid membrane are determined by the localization of the non-polar polyene chain, and by the localization of the hydrophilic groups, which remain in contact with the polar head groups of the lipid bilayer [40].…”
Section: Macula Lutea Pigmentsmentioning
confidence: 99%
“…It has also been found in human lenses. The lutein-binding protein (qlLBP) was found and purified from quail liver, but has not yet been described in detail [53]. As both the macular pigments and canthaxanthin dissolve well in lipids and are frequently delivered unchanged to ocular tissues, it has been suggested that there is a high probability that they may follow the same absorptive pathways as other dietary lipids [54,55].…”
Section: Mechanisms Of Canthaxanthin Delivery To the Macula Lutea Memmentioning
confidence: 99%
“…Until recently, it was believed that all animals are incapable of synthesizing them de novo, and must acquire them from the diet (Bhosale and Bernstein, 2007;Goodwin, 1986). However, Moran and Jarvik (2010) reported the presence of carotenoid biosynthetic genes in aphids, which appear to have been laterally transferred from fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Other pigmentbinding proteins are less well known. Although carotenoid-binding protein (CBP) has been well studied in vertebrates (Bhosale and Bernstein 2007), few homologs have been recognized among the Lepidoptera. In Lepidoptera, the yellow-blood mutant (Y) of B. mori (which produces yellow cocoon) was identified (Tsuchida and Sakudoh 2015); however, the expression of BmCBP was not detected in the epidermis.…”
Section: Species-specificmentioning
confidence: 99%